Rugoscopia palatina como método de identificación en odontología forense. Revisión bibliográfica - Moreno Hidalgo, Odalys Nagely (2022)
Palatal roughoscopy is considered a diagnostic method based on; the study of the size, shape, position, and distribution of palate components, such as palatal wrinkles. In favor of forensic identification processes, these roughnesses behave similarly to fingerprints; they do not change during the individual's lifetime and have considerable advantages and benefits since the palate is a privileged area, especially in the protection against trauma due to its position in the oral cavity. They are not affected by prosthetic appliances; while dental replacement occurs, or according to the partial or total loss of teeth, they do not vary; during orthodontic and maxillary orthopedic treatments are not considerably altered, and the tongue avoids the occurrence of blows. The following bibliographic research focused on analyzing palatal roughoscopy as a method of identification in forensic dentistry, employing a bibliographic review of the last ten years. We considered twenty-five bibliographic sources in Spanish, English, and Portuguese compiled in databases such as Pubmed/Medline, Lilacs, Lipecs, Ncbi, ResearchGate, ScienceDirect, Google Scholar, and National and International Bibliographic Repositories between the years 2012 and 2022. In this review, we obtained that the most employed method for the utilization of this identification technique is the analysis of plaster models together with the systems of Bassauri and Trobo Hermosa, which also emphasizes the great importance and advantage it has at the time of solving cases related to burns. The most frequent type of palatal cleft is the sinuous cleft, followed by the straight palatal cleft, and the less frequently used is the circle type, which is variable and independent of sex. The most reported limitations are the lack of ante mortem records, bony palate malformations, cephalic crushing, and advanced decomposition